ON THE NORMAL STRESSES IN THE ELASTIC BODY WITH A LOCALLY CURVED FIBRE UNDER GEOMETRIC NONLINEAR STATEMENT - Kosker, Resat; Simsek, Kadriye (YILDIZ TECHNICAL UNIV, 2006)
In the framework of the piecewise homogeneous body model with the use of the three-dimensional geometrically nonlinear exact equations of the theory of elasticity, the method developed for the determination of the stress distribution in the unidirectional fibrous composites with locally curved fibres is used to investigate related normal stresses for the case where the interaction between the fibres is not taken into account. All investigations are made for an infinite elastic body containing a single locally curved fibre. Under uniaxial loading along the fibre the normal stresses acting on the interface are studied and the numerical results illustrated the effect of the geometrical nonlinearity on the distribution of the stresses are presented. Keywords: Unidirectional fibrous composite, local curving, geometrical nonlinearity, normal stresses.
Keywords: Unidirectional fibrous composite; local curving; geometrical nonlinearity; normal stresses; Engineering